Fungi-assisted bio-flocculation for microalgae harvesting: Literature-guided optimization and experimental evaluation using Aspergillus awamori - Jesna Fathima; Ajesh M. Arjun; Pritha Chatterjee (Biocatalysis and Agricultural Biotechnology, 2026)

Colonoscopy findings in CDH1 carriers from a multicenter international study - Arjun Chatterjee; Robert Hüneburg; Qijun Yang; Shannon Morrison; Anna Bettzüge; Tim Marwitz; Stefan Aretz; Isabel Spier; Tim Ripperger; Silke Redler; Mykyta Kachanov; Alexander E. Volk; et al. (Familial Cancer, 2025)
Germline (likely-)pathogenic variants (PV) in CDH1 predispose carriers to hereditary diffuse gastric cancer and lobular breast cancer. Previous studies from the United States suggest CDH1 variant carriers have an increased risk for adenomas or sessile serrated lesions (SSL), yet data linking CDH1 PVs and colorectal neoplasia are scarce. We aimed to investigate colonoscopy findings in CDH1 PVs. Adults carrying a PV/LPV in CDH1 with ≥ 1 colonoscopy between 01/01/2004–12/31/2023 were included. Patients were sourced from the David G. Jagelman Inherited Colorectal Cancer Registries at Cleveland Clinic and the German Consortium for Familial Intestinal Cancer. 103 CDH1 PV carriers were included. Most were female (66%) and white (93.1%). The median age at first colonoscopy was 47 years. The adenoma detection rate (ADR) was 29.4% (95% CI:19.9–41.1%) in the German cohort and 48.6% (95% CI: 33.0-64.4%) in the Cleveland cohort ( p = 0.055) and significantly correlated with age (< 45 years, 13.6% (95% CI: 6.40–26.7%); 45–49 years, 52.4% (95% CI: 32.4–71.7%); ≥50 years, 52.6% (95% CI: 37.3–67.5%); p < 0.001). The ADR in Cleveland was higher than the U.S. average ADR but the difference was not statistically significant (48.6% vs. 35.6%, p = 0.08), and the ADR in the German cohort (29.4%) was similar to the national German average risk screening cohort (31.3% in men, p = 0.84; 20.1% in women, p = 0.08). In our screening cohort with CDH1 PV carriers, we demonstrated an ADR of 13.5% in individuals under 45 years, similar to the ADR in patients aged 25–40 years with a family history of CRC. Overall, SSL detection rate was 9.7%. Colorectal cancer was diagnosed in 3 patients (3.2%), 2/3 with an early age of onset before the age of 50 years. This first international study provides preliminary evidence of a higher ADR in U.S. CDH1 PV carriers compared to the general population, with a high number of adenomas detected before the age of 50. This may indicate an increased CRC risk that should be explored in larger studies.

Endoscopic screening for identification of signet ring cell gastric cancer foci in carriers of germline pathogenic variants in CDH1 - Lady Katherine Mejia Perez; Margaret O’Malley; Arjun Chatterjee; Ruishen Lyu; Qijun Yang; Michael W. Cruise; Lisa LaGuardia; David Liska; Carole Macaron; R. Matthew Walsh; Carol A. Burke (Familial Cancer, 2024)
To determine the preoperative detection of signet ring cancer cells (SRC) on upper endoscopy (EGD) in patients with CDH1 pathogenic variant (PV) undergoing gastrectomy. To evaluate the development of advanced diffuse gastric cancer (DGC) in patients choosing surveillance. Guidelines recommend prophylactic total gastrectomy (pTG) in CDH1 PV carriers with family history of DGC between 18 and 40 years. Annual EGD with biopsies according to established protocols is recommended in carriers with no SRC and no family history of DGC, with consideration of pTG. Retrospective analysis of asymptomatic patients with CDH1 PVs with ≥ 1 surveillance EGD. Outcomes included pre-operative EGD detection of SRC, surgical stage, and progression to advanced DGC in those electing surveillance with EGD. 48 patients with CDH1 PVs who had ≥ 1 EGD were included. 24/ 48 (50%) underwent gastrectomy, including pTG in 7 patients. SRCC were detected on gastrectomy specimen in 21/24 (87.5%). SRCs were identified by EGD in 17/21 patients who had SRCC on gastrectomy specimens (sensitivity 81%, 17/21). All cancers were stage pT1a. The remaining 17 patients (50% with a family history of gastric cancer) continue in annual EGD surveillance with a median follow-up of 34.6 months. No SRCC or advanced DGC have been diagnosed. No CDH1 PV carriers without SRCC on random biopsies followed in an endoscopic program developed advanced DGC over a median follow up of 3 years. In the short term, EGD surveillance might be a safe alternative to immediate pTG in experienced hands in referral centers.

Identification of Potentially Repurposable Drugs for Lewy Body Dementia Using a Network-Based Approach - Megha Manoj; Siddarth Sowmyanarayan; Arjun V. Kowshik; Jhinuk Chatterjee (Journal of Molecular Neuroscience, 2024)

The Association of Respiratory Symptoms and Indoor Housing Conditions Among Migrant Farmworkers in Eastern North Carolina - Gregory D. Kearney; Arjun B. Chatterjee; Jennifer Talton; Haiying Chen; Sara A. Quandt; Phillip Summers; Thomas A. Arcury (Journal of Agromedicine, 2014)

To be or not to be social: foraging associations of free-ranging dogs in an urban ecosystem - Sreejani Sen Majumder; Anandarup Bhadra; Arjun Ghosh; Soumitra Mitra; Debottam Bhattacharjee; Jit Chatterjee; Anjan K. Nandi; Anindita Bhadra (acta ethologica, 2014)

A Cross-Sectional Exploration of Excessive Daytime Sleepiness, Depression, and Musculoskeletal Pain among Migrant Farmworkers - Joanne C. Sandberg; Joseph G. Grzywacz; Jennifer W. Talton; Sara A. Quandt; Haiying Chen; Arjun B. Chatterjee; Thomas A. Arcury (Journal of Agromedicine, 2012)

Depressive Symptoms and Sleepiness Among Latino Farmworkers in Eastern North Carolina - Joseph G. Grzywacz; Arjun B. Chatterjee; Sara A. Quandt; Jennifer W. Talton; Haiying Chen; Maria Weir; Thomas A. Arcury (Journal of Agromedicine, 2011)